Geodesics without conjugate points and curvatures at infinity - MENDONÇA,SÉRGIO (2000)
We study the asymptotic behavior of curvature and prove that the integral of curvature along a geodesic without conjugate points is nonpositive and some generalizations of Myers theorem and Cohn-Vossen's theorem. Some applications are also given.